Theophylline inhibits the cough reflex through a novel mechanism of action() - Dubuis, Eric (Mosby, 2014)
BACKGROUND: Theophylline has been used in the treatment of asthma and chronic obstructive pulmonary disease for more than 80 years. In addition to bronchodilator and anti-inflammatory activity, clinical studies have suggested that theophylline acts as an antitussive agent. Cough is the most frequent reason for consultation with a family doctor, and treatment options are limited. Determining how theophylline inhibits cough might lead to the development of optimized compounds. OBJECTIVE: We sought to investigate the inhibitory activity of theophylline on vagal sensory nerve activity and the cough reflex. METHODS: Using a range of techniques, we investigated the effect of theophylline on human and guinea pig vagal sensory nerve activity in vitro and on the cough reflex in guinea pig challenge models. RESULTS: Theophylline was antitussive in a guinea pig model, inhibited activation of single C-fiber afferents in vivo and depolarization of human and guinea pig vagus in vitro, and inhibited calcium influx in airway-specific neurons in vitro. A sequence of pharmacological studies on the isolated vagus and patch clamp and single-channel inside-out experiments showed that the effect of theophylline was due to an increase in the open probability of calcium-activated potassium channels. Finally, we demonstrated the antitussive activity of theophylline in a cigarette smoke exposure model that exhibited enhanced tussive responses to capsaicin. CONCLUSION: Theophylline inhibits capsaicin-induced cough under both normal and “disease” conditions by decreasing the excitability of sensory nerves through activation of small- and intermediate-conductance calcium-activated potassium channels. These findings could lead to the development of optimized antitussive compounds with a reduced side effect potential.